Silver‐Doped Zinc Oxide as a Nanofiller for Development of Poly(vinyl alcohol)/Poly(vinyl pyrrolidone) Blend Nanocomposites. Issue 1 (8th January 2016) - Ramesan, M. T.; Varghese, Meghana; P, Jayakrishnan; Periyat, Pradeepan
ABSTRACT: Nanocomposites of poly(vinyl alcohol) (PVA)/poly(vinyl pyrrolidone) (PVP)/silver‐doped zinc oxide (Ag‐doped ZnO) ternary blends were prepared and characterized by Fourier transform infrared (FTIR) spectroscopy, ultraviolet (UV), scanning electron microscopy (SEM), X‐ray diffraction (XRD), Differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and conductivity studies. The FTIR and UV spectrum indicated the intermolecular interaction between the polar part of blend and the metal oxide nanoparticles. SEM and XRD patterns ascertained the structurally ordered arrangements of nanoparticles within the polymer matrix. The DSC results showed that the addition of Ag‐doped ZnO particles to PVA/PVP decreases the thermal behavior such as glass transition and melting temperature of the blend. The TGA study indicated that the composites attained better thermal resistance than a pure blend and the thermal stability of the composite increases with an increase in the concentration of nanoparticles. The electrical properties such as AC conductivity and dielectric properties of the composites were increased with an increase in content of nanoparticles up to a certain concentration (5 wt%), and thereafter the value was found to decrease.